Strategic shirking in competitive labor markets: A general model of multi‐task promotion tournaments with employer learning. Issue 2 (23rd February 2020) - DeVaro, Jed; Gürtler, Oliver
Abstract: In a multitask, market‐based promotion tournament model, under different environments concerning employer learning about worker ability, it is shown that: (a) asymmetric learning in multitask jobs is a necessary condition for "strategic shirking" (i.e., underperforming on certain tasks to increase the promotion probability); (b) when learning becomes increasingly symmetric on one task, the effort allocated to that task could increase or decrease, but effort on the other task increases; (c) strategic shirking does not occur in equilibrium in single‐task models; and (d) promotions signal worker ability even when there is symmetric learning on one task, if learning is asymmetric on another.